2018
DOI: 10.1002/2211-5463.12384
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal extracellular pH values alter DNA damage response to induced double‐strand breaks

Abstract: Conditions leading to unrepaired DNA double‐stranded breaks are potent inducers of genetic instability. Systemic conditions may lead to fluctuation of hydrogen ions in the cellular microenvironment, and we show that small variations in extracellular pH , termed suboptimal pH e, can decrease the efficiency of DNA repair in the absence of intracellular pH variation. Recovery from bleomycin‐induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Recovery from sublethal DNA damage induced by other stressors is also inhibited at acidic pH o (with associated low pH i ), leading to accumulation of chromosomal aberrations (27). Even subtle decreases in pH o significantly delay repair of double-stranded DNA breaks in noncancer cells (28). Taken together, acidic stress in a preneoplastic setting may increase genetic instability and hence the risk of transition to cancer.…”
Section: Genetic and Epigenetic Changesmentioning
confidence: 99%
“…Recovery from sublethal DNA damage induced by other stressors is also inhibited at acidic pH o (with associated low pH i ), leading to accumulation of chromosomal aberrations (27). Even subtle decreases in pH o significantly delay repair of double-stranded DNA breaks in noncancer cells (28). Taken together, acidic stress in a preneoplastic setting may increase genetic instability and hence the risk of transition to cancer.…”
Section: Genetic and Epigenetic Changesmentioning
confidence: 99%
“…Aside from hypoxia, low pH is considered another potential factor in “microenvironment‐induced mutagenesis” . Acidosis indeed impairs DNA repair mechanisms, thereby promoting genetic instability and sensitizing cells to other mutagens such as UV irradiation . Beyond that, elevated proton extrusion can cause dysplasia irrespective of oncogene status .…”
Section: Genetic Alterations During Melanoma Initiation and Progressionmentioning
confidence: 99%
“…Pre-mutational factors, specifically hypoxia and altered intracellular pH, are crucial for creating a conducive microenvironment for transformational changes, leading to the accumulation of genetic alterations. Importantly, a correlation between higher levels of hypoxia, pH, and a higher number of driver mutations has been observed in various types of cancer (4547). We showed that the high expression of hypoxia gene signatures, such as HIF1A , VEGFA , TMX1 , and TGFBI , among others, in hypermetabolic lesions positively correlates with APOBEC signature genes.…”
Section: Discussionmentioning
confidence: 99%